A graphics tablet as a teaching tool - Kurashkin, O. (ТДАТУ, 2019)
The article is devoted to the aspects of using of graphics tablets on ESP lessons by students of agro-technological specialties. The main prerequisites for the implementation of interactive teaching methods are determined. The importance of IC-technologies implementation into the educational process and its significance for raising students’ learning and cognitive activity and motivation are highlighted and clarified.
Keywords: graphics tablets; ESP; the importance of IC-technologies; interactive learning technologies